Explaining Research: How to Reach Key Audiences to Advance Your Work (Oxford University Press, 2010)
Explaining Research is the first comprehensive communications guidebook for scientists, engineers, and physicians. Drawing on knowledge gleaned from a forty-year career in research communications, Dennis Meredith maps out how scientists can utilize sophisticated tools and techniques to disseminate their discoveries to important audiences. He explains how to use websites, blogs, videos, webinars, old-fashioned lectures, news releases, and lay-level articles to reach key audiences, emphasizing along the way that a strong understanding of the audience in question will allow a more effective communication tailored to a unique background and set of needs. In addition to drawing on the experience of the author, the book also includes excerpts from interviews with 45 of the country\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\'s leading science communications experts, including academics, authors, journalists, and public information officers. As the \\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\information age\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\ places new demands on scientists, Explaining Research will be a valuable resource not only for current professional scientists, but also for students who are the voice of the science community\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\'s next generation. This authoritative guide shows how to: Ãƒâ€šÃ,Â· Develop a \\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\strategy of synergy\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\ that makes research communication efficient and effective Ãƒâ€šÃ,Â· Give compelling talks Ãƒâ€šÃ,Â· Build a professional Web site Ãƒâ€šÃ,Â· Create quality posters, photos, animations, videos, e-newsletters, blogs, podcasts, and Webinars Ãƒâ€šÃ,Â· Write popular articles and books Ãƒâ€šÃ,Â· Persuade donors, administrators and other key funding decision-makers Ãƒâ€šÃ,Â· Produce news releases that attract media coverage Ãƒâ€šÃ,Â· Give clear media interviews Ãƒâ€šÃ,Â· Serve as a public educator in schools and science centers Visit www.explainingresearch.com to learn more about the book and additional resources.